In Vitro and In Vivo Test of Boron Delivery Agent for BNCT - Sista Dyah Wijaya; Bagaswoto Poedjomartono; Yohannes Sardjono (Indonesian Journal of Physics and Nuclear Applications, 2019)
BNCT is an alternate therapy for treating cancer. The principle of BNCT involves a neutron boron uptake and a fission reaction that produce alpha particles and Li ions with a high level of linear energy transfer in the tissue. It is effective in killing tumor cells. To administer boron in the tumor cells, a boron delivery agent is needed. Thus far, there are a variety of boron delivery agents that have been developed. To date, just two main boron-based drugs, BPA and BSH, have been used for clinical studies. Many other boron delivery agents have been evaluated in vivo and in vitro but have not been evaluated clinically. Therefore, the other boron delivery agents have not been used in BNCT clinical studies.